Utilization of Wordwall Media in Arabic Vocabulary Learning Towards Eighth Graders - Hajar, Ibnu; Muassomah, Muassomah; Muhlis, Wachida; Bani Sa'id, Sa'id Al Zaiim; Fitra, Muhammad Naufal (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2024)
Wordwall is an interesting, interactive, and educational browser game application. This application can be an interesting learning resource, media, and assessment tool for students. This research aims to determine the application of Wordwall media and determine students' responses to learning Arabic vocabulary using Wordwall media in eighth grade at MTs Satu Atap Al-Hidayah Batu. A quantitative approach and survey methods were used in this research. Data collection was carried out through observation, interviews, and questionnaires. The data collected was eventually analyzed by using descriptive statistics. Descriptive analysis was carried out with the SPSS 25 application. The research results showed that the ideal total score for all items is the number of questionnaires 9 X Maximum score 18 for each score = 162. The total score obtained from the research = 116. The students’ responses about Wordwall media as a learning media for Arabic vocabulary are considered positive because the percentage value obtained is 71.60%. It was confirmed that the significance of Wordwall as an innovative learning tool and the positive response from students, providing a basis for increasing the use of technology in educational contexts.